Organizational Health Literacy: Review of Theories, Frameworks, Guides, and Implementation Issues - Elina Farmanova PhD; Luc Bonneville PhD; Louise Bouchard PhD (SAGE Publishing, 2018)
Organizational health literacy is described as an organization-wide effort to transform organization and delivery of care and services to make it easier for people to navigate, understand, and use information and services to take care of their health. Several health literacy guides have been developed to assist healthcare organizations with this effort, but their content has not been systematically reviewed to understand the scope and practical implications of this transformation. The objective of this study was to review (1) theories and frameworks that inform the concept of organizational health literacy, (2) the attributes of organizational health literacy as described in the guides, (3) the evidence for the effectiveness of the guides, and (4) the barriers and facilitators to implementing organizational health literacy. Drawing on a metanarrative review method, 48 publications were reviewed, of which 15 dealt with the theories and operational frameworks, 20 presented health literacy guides, and 13 addressed guided implementation of organizational health literacy. Seven theories and 9 operational frameworks have been identified. Six health literacy dimensions and 9 quality-improvement characteristics were reviewed for each health literacy guide. Evidence about the effectiveness of health literacy guides is limited at this time, but experiences with the guides were positive. Thirteen key barriers (conceived also as facilitators) were identified. Further development of organizational health literacy requires a strong and a clear connection between its vision and operationalization as an implementation strategy to patient-centered care. For many organizations, becoming health literate will require multiple, simultaneous, and radical changes. Organizational health literacy has to make sense from clinical and financial perspectives in order for organizations to embark on such transformative journey.